Alcohol use disorders and antiretroviral therapy among prisoners in Argentina. - Alpert, Michael; Wickersham, Jeffrey A; Vázquez, Mariana; Altice, Frederick L (International journal of prisoner health, 2013)
While Argentina has significantly improved access to HIV care and antiretroviral therapy (ART) for both the general population and prisoners, the prevalence of alcohol use disorders (AUDs) among HIV-infected prisoners and their relationship to accessing ART in Argentina is currently unknown. This study aims to characterize the substance abuse patterns of HIV-infected prisoners in Argentina and to assess the independent correlates of receipt of pre-incarceration ART.
Keywords: Adolescent; Adult; Alcoholism; Anti-Retroviral Agents; Argentina; Cross-Sectional Studies; Female; HIV Infections; Humans; Male; Prevalence; Prisoners; Questionnaires; Young Adult